FEATURES OF THE KAZAKH LANGUAGE'S TERMINOLOGY (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
Thousands of new terms are created as science and technology progress. Finding the internal sources and techniques used to create terms, as well as the distinctive qualities of each one that are utilized to create each new concept based on the national language, is especially crucial. In addition, every language borrows words and phrases from other languages. It is quite difficult to find a language that does not take words and phrases from another language. This paper explored the characteristics of Kazakh terminology. The formation and development of Kazakh terminology as a science were analyzed step by step. The rules and principles of the construction of the national terminology database were comprehensively explained. In addition, the work of the Alash intelligentsia in the formation of the Kazakh scientific language was introduced.